Hubungan Perilaku Merokok dan Komorbid dengan Lama Rawat Inap Pasien PPOK di RSUD Al Ihsan Bandung tahun 2019-2021 - Alda Alysia Jaswirna; Siska Nia Irasanti; Ganang Ibnusantosa (UNISBA Press, 2023)
Abstract. Chronic obstructive pulmonary disease (COPD) is a disease with airflow limitation caused by an abnormal inflammatory response in the lungs and is characterized by a decrease in the FEV1/FVC ratio below 0.7 postbronchodilator. In the world, the prevalence of COPD is 174 million people in 2015, in Indonesia it is 3.7% per mil, and in West Java COPD ranks second highest after asthma. COPD risk factors include genetics, age, gender, comorbidities, smoking, and occupation. These risk factors can have an impact not only on the incidence of COPD, but also on the length of stay of COPD. This study aims to determine the relationship between smoking behavior, age, and comorbidities with the length of stay of COPD patients at Al Ihsan Hospital in Bandung in 2019-2021. This type of research is quantitative with analytic observational method and cross sectional approach design. The instrument used is a medical record. In this study, data were obtained from 60 medical records of COPD patients using random sampling technique. The data analysis used was univariate and chi square test for bivariate analysis. Statistical test results showed that 68.3% of patients smoked, 81.7% of elderly patients, and 76.7% of patients had comorbidities. The results showed that there was a significant relationship between smoking behavior and the length of stay of COPD patients with p-value= 0.013 (p <0.05), and there is a significant relationship between comorbidities and length of stay of COPD patients with p-value= 0.004 (p <0.05). It is recommended to carry out health promotion and prevention related to risk factors associated with COPD length of stay such as smoking behavior, age, and comorbidities. Abstrak. Penyakit paru obstruktif kronik (PPOK) adalah suatu penyakit dengan keterbatasan aliran udara disebabkan oleh respon inflamasi abnormal paru-paru dan ditandai dengan penurunan rasio FEV1/FVC di bawah 0,7 pascabronkodilator. Di dunia prevalensi PPOK 174 juta orang tahun 2015, di Indonesia 3,7% per mil, dan di Jawa Barat PPOK menempati peringkat tertinggi kedua setelah asma. Faktor risiko PPOK di antaranya genetik, usia, jenis kelamin, komorbid, merokok, dan pekerjaan. Faktor risiko tersebut dapat berdampak tidak hanya pada kejadian PPOK, tetapi juga pada lama rawat inap PPOK. Penelitian ini bertujuan untuk mengetahui hubungan perilaku merokok, usia, dan komorbid dengan lama rawat inap pasien PPOK di RSUD Al Ihsan Bandung pada tahun 2019-2021. Jenis penelitian ini adalah kuantitatif dengan metode observasional analitik dan rancangan pendekatan cross sectional. Instrumen yang digunakan berupa rekam medis. Pada penelitian ini didapatkan data sebanyak 60 rekam medis pasien PPOK dengan teknik random sampling. Analisis data yang digunakan adalah univariat dan uji chi square untuk analisis bivariat. Hasil uji statistik menujukkan 68,3% pasien merokok, 81,7% pasien adalah lansia, dan 76,7% pasien memiliki komorbid. Hasil penelitian menunjukkan bahwa terdapat hubungan yang bermakna antara perilaku merokok dengan lama rawat inap pasien dengan p-value= 0,013 (p <0,05), dan terdapat hubungan yang bermakna antara komorbid dengan lama rawat inap pasien dengan p-value= 0,004 (p <0,05). Disarankan melakukan promosi kesehatan dan pencegahan berkaitan dengan faktor-faktor risiko yang berhubungan dengan lama rawat inap PPOK seperti perilaku merokok, usia, dan komorbid.